MCTS : Microsoft Office Sharepoint Server 2007 configuration study guide (70-630) - Pyles, James (Serious skills., 2008)
Qualified SharePoint administrators are in demand, and what better way to show your expertise in this growing field than with Microsoft's new MCTS: Microsoft Office SharePoint Server 2007, Configuration certification. Inside, find everything you need to prepare for exam 70-630, including full coverage of exam topics-such as configuring content management, managing business intelligence, and more-as well as challenging review questions, real-world scenarios, practical exercises, and a CD with advanced testing software. For Instructors: Teaching supplements are available for this title.